(untitled) (Scientific journal of the Fergana State University, 2024)
The article describes methods of management of the superterrestrial composition of the horsetail of the field, growing in the wild on the grassland-grey-earth plains of the Fergon valley. The results were presented in the form of tables and diagrams. Vitamins were studied with chromatography in effective treatment.